Percepção de risco ambiental da produção de petróleo no município de Carmópolis, SE - Guimarães, Ana Maria dos Santos (2017)
One of the most meaningful impacts on environment by human activities is related to the extraction of mineral wealth from the underground, such as oil and natural gas, which may provoke from the suppression of the native forest to implement projects, to social impacts. In the city of Carmópolis, Sergipe, where the exploration and production of oil and natural gas present themselves as the main economic activity, there are only 3,41% of the original native vegetation, which characterizes the compromised natural balance of the ecosystems and life quality of the local population. In this sense, studies that bring an analysis over environmental risks of oil activity, examining social perception of the risks, as well as the effectiveness of legal instruments to intimidate impacts, may rise essential reflections to the subject. Thus, the general objective of this research was to analyze the environmental and technological perception of risks from the inhabitants of the city of Carmópolis, Sergipe. Besides that, it was aimed at analyzing the effectiveness of the National Environmental Policy in the area studied, from the legal instrument of the environmental licensing, as well as Public Civil Actions. The methodology used was based on gathering primary data, with semi structured interviews with the inhabitants of the city, selected by probabilistic sample; and also secondary data from the bibliographical and document research at the environmental agency responsible for the licensing of oil activity in the state. The results have shown that the environmental risk is noticed by the local population, however it is tolerated due to the benefits of the oil activity, or under a different approach, due to the strong economic dependence the population is under, making the adjustments to risky situations to be neglected. On the other hand, the situation of establishment of the National Environmental Policy in Carmópolis still presents many critical points that differ from the objectives of this policy and drive the city out of an efficient and integrated environmental management. It is necessary to understand the environmental problem from the political perspective, and under this view, all the efforts to strengthen participative democracy which contribute to changing this scenario in the search for care with nature.